Appreciations, with an Essay on Style - Pater, Walter, 1839-1894 (Salt Lake City, UT : Project Gutenberg, 2003)
"Appreciations, with an Essay on Style" by Walter Pater is a collection of critical essays written during the late 19th century. It explores the nuances of literary style, particularly the distinction and interplay between prose and poetry, while also providing assessments of various poets and writers, including Wordsworth and Coleridge. The book delves into the complexities of literary appreciation, emphasizing the beauty and artistry present in both forms of writing. The opening of the text establishes a philosophical foundation for Pater's aesthetic views, discussing the importance of differentiating between various forms of art to fully understand their merits. Pater argues against the overly restrictive classifications of literary styles, advocating for recognition of the imaginative elements inherent in both prose and poetry. He emphasizes that good art emerges from the truthful expression of a writer$1 (Bs unique sensibility and perception of the world. Through this lens, Pater lays the groundwork for the subsequent analysis of specific literary figures, demonstrating how the intricacies of language and style reflect deeper truths and emotions. (This is an automatically generated summary.)s
Style -- Wordsworth -- Coleridge -- Charles Lamb -- Sir Thomas Browne -- "Love's labours lost -- "Measure for measure." -- Shakespeare's English kings -- Dante Gabriel Rossetti -- Feuillet's "La morte" -- Postscript.
Unaccented version in 7awae10.txt and 7awae10.zip, accented versions in 8awae10.txt and 8awae10.zip
Release date is 2003-05-01
Produced by Alfred J. Drake. HTML version by Al Haines.
Keywords: English literature -- History and criticism; Style, Literary